Evolutionary Psychology: Interfaces between Natural Selection and Human Behavior - Cecconello, William Weber; Ferreira, Vinícius Renato Thomé (Revista de Psicologia da IMED, 2014)
The theory of evolution by natural selection postulates that involuntary adaptations in species gave them advantage for survival and reproduction, so the creatures that had the characteristics that made them better adapted to their niche were able to pass on their genes, and thus perpetuate the specie. In the evolutionary perspective, the brain is an organ that has evolved over millions of years to solve problems related to survival and reproduction in the same way as other body parts also came under pressure from natural selection. Understanding how the processes occurred and how natural selection has refined our skills and behavioral consequences has been the aim of Evolutionary Psychology. This article aims, through a narrative review, to describe the evolutionary psychology and its relevance to the understanding of human behavior. For this purpose, this article was composed by topics that may help in understanding this field of study and its applicability in psychology. Possibly the challenge remains to Latin American psychology is not just integrate Evolutionary Psychology effectively in academic teaching , but to ensure that dialogues between areas of knowledge which differ and that permit a more complete understanding of the human being.